(20$ \bar 2 $1) MOVPE and HVPE GaN grown on 2″ patterned sapphire substrates. Issue 3 (22nd January 2014) - Meisch, Tobias; Alimoradi‐Jazi, Maryam; Klein, Martin; Scholz, Ferdinand
Abstract: (20‐21) GaN was grown on (22‐43) patterned sapphire substrates by MOVPE and subsequently overgrown in a HVPE growth step. By using fairly c‐plane growth conditions and adjusting the reactor temperature of the particular layers, GaN stripes free of any parasitic islands were grown by MOVPE. X‐ray measurements confirmed a very promising crystal quality. It turned out, that the stripes are formed by (10‐11) and (0001) facets, which seems to be the most stable facets during growth. Via HVPE overgrowth, the single stripes coalesce and form a flaky surface. A fairly high growth rate of about 142 μm per hour was achieved. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)